Mesin Penetas Telur Menggunakan Microcontroller ATMega328 Berbasis Arduino - Iwan Purnama; Ambiyar Ambiyar; Fahmi Rizal; Unung Verawardina; Sutrino Dwi Raharjo; Abdul Karim (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The purpose of this study was to design and implement a duck egg incubator. An egg incubator is a machine that functions to take over the incubation task of a duck mother in incubating fertilized eggs from the result of crossing or mating with a male. The existing incubators work in temperature control, reversing the egg racks, but do not use an egg informing system that has been hatched. In designing this duck egg incubator based on Arduino as a controller. The temperature used must be measured by the resistance of the space or the approximate resistance of the eggs to hatch. The microcontroller used is the ATMega328 integrated on the Arduino Uno, temperature sensor, humidity sensor, humidity control system and other supporting components using Arduino. The test was carried out by comparing the DS18B20 temperature sensor with a Thermometer with an error difference of 0.15. The result of this research is the device can control the temperature not exceeding 39 ° C for hatching eggs. The device has 2 usage buttons, namely a start button (green) to perform hatching day calculations and a reset button (red) to stop hatching day calculations. The day variable that has been running is still stored in the microcontroller EEPROM (Electrically Erasable Programmable Read-Only Memory) so that if there is a disconnection or loss of a voltage power source such as a power failure and so on. The 12VDC fan on the device turns on every 30 minutes and goes out for the next 30 minutes